Amphetamine Drug Analysis Using Raman Spectroscopy - Yaser Zuhair Tawfiq (Journal of Global Pharma Technology, 2019)
The main concept of this work is to analyze the illegal amphetamine drug by Raman spectroscopy. The samples of amphetamine were obtained from the drug control office in Iraq. Two different forms of amphetamine samples (a full tablet 167mg, and powder167mg) were chosen to investigate the sensitivity of Raman spectroscopy. The spectral of the two samples show no difference, and the amount of material does not constitute an obstacle in the way of measurements. The Raman shift spectrum of two forms has been reported in the region 2969.2 cm-1 for the powder form and 3009 cm-1 for the tablet form.Keywords: Raman spectroscopy, Amphetamine, Drugs.